Rural and urban linkages: Operation flood’s role in India’s dairy development - Cunningham, Kenda (International Food Policy Research Institute, 2009)
Between 1970 and 2009, India has overcome many infrastructural, market, and institutional challenges to transition from a dairy importing nation to the top producer in the world of both buffalo and goat milk, as well as the sixth largest producer of cow milk. In India, at least 100 million households are involved in farming and 70 million have dairy cattle. In India, dairy production is important for employment, income levels, and the nutritional quality of diets. Milk production in India is dominated by smallholder farmers including landless agricultural workers. For example, 80 percent of milk comes from farms with only two to five cows. A well-known smallholder dairy production initiative, Operation Flood, laid the foundation for a dairy cooperative movement that presently ensures returns on dairy investments to 13 million members. Operation Flood also advanced infrastructural improvements to enable the procurement, processing, marketing, and production of milk and to link India’s major metropolitan cities with dairy cooperatives nationwide. This intervention transformed the policy environment, brought significant technological advancements into the rural milk sector, established many village cooperatives, and oriented the dairy industry toward markets.